2005
DOI: 10.1291/hypres.28.925
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Mechanisms of Spironolactone Associated with the Angiotensin-Converting Enzyme/Epidermal Growth Factor Receptor/Extracellular Signal-Regulated Kinases, NAD(P)H Oxidase/Lectin-Like Oxidized Low-Density Lipoprotein Receptor-1, and Rho-Kinase Pathways in Aldosterone/Salt-Induced Hypertensive Rats

Abstract: Studies were performed to test the hypothesis that the angiotensin-converting enzyme (ACE)/

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 50 publications
(56 reference statements)
4
71
0
3
Order By: Relevance
“…Previously, EGFR signaling has been reported to be affected by several antihypertensive therapies such as renin-angiotensin system inhibitors, endothelin 1 receptor antagonists, and antioxidants (Fujino et al, 1998;Dorrance et al, 2001;Nakano et al, 2005;Portik-Dobos et al, 2006), which matches the observed decrease in pEGFR expression in lisinopril-treated 5/6Nx animals. Moreover, the ACE inhibitor imidapril (Nakano et al, 2005), the AT 1 R antagonist losartan (Lautrette et al, 2005), and the aldosterone antagonist spironolactone ) also affect EGFR signaling.…”
Section: Chronic Egfr Inhibition Prevents Hypertensionsupporting
confidence: 76%
See 1 more Smart Citation
“…Previously, EGFR signaling has been reported to be affected by several antihypertensive therapies such as renin-angiotensin system inhibitors, endothelin 1 receptor antagonists, and antioxidants (Fujino et al, 1998;Dorrance et al, 2001;Nakano et al, 2005;Portik-Dobos et al, 2006), which matches the observed decrease in pEGFR expression in lisinopril-treated 5/6Nx animals. Moreover, the ACE inhibitor imidapril (Nakano et al, 2005), the AT 1 R antagonist losartan (Lautrette et al, 2005), and the aldosterone antagonist spironolactone ) also affect EGFR signaling.…”
Section: Chronic Egfr Inhibition Prevents Hypertensionsupporting
confidence: 76%
“…Moreover, the ACE inhibitor imidapril (Nakano et al, 2005), the AT 1 R antagonist losartan (Lautrette et al, 2005), and the aldosterone antagonist spironolactone ) also affect EGFR signaling. Thus, our observation that PKI-166 treatment successfully lowered blood pressure in …”
Section: Chronic Egfr Inhibition Prevents Hypertensionmentioning
confidence: 99%
“…There is a large body of evidence showing an activation of extracellular signal-related kinase-1/2 in response to many known hypertropic agonists. 48,49 However, Purcell et al 50 have recently shown that extracellular signal-related kinase-1/2 signaling is not required for mediating physiological or pathological cardiac hypertrophy in vivo; moreover, blockade or deletion of cardiac Figure 5 Cluster analysis of genes selectively normalized by QHI in late LVH. The transcripts differentially expressed in late LVH were then filtered to select out those selectively normalized by the QHI treatment group and average linkage hierarchical cluster analysis of this cohort was then performed to graphically illustrate their expression profile.…”
Section: Signal Transductionmentioning
confidence: 99%
“…In the kidney, aldosterone via MR additionally induces mesangial cell proliferation via ROS-dependent activation of EGFR, leading to combined ERK1/2 and PI3K/mTOR signaling ). There is a close interaction between genomic and nongenomic aldosterone signaling because aldosterone/MR can both transactivate the EGFR and enhance its expression (Dorrance et al 2001, Nakano et al 2005, Meinel et al 2013. Furthermore, nongenomic aldosterone-mediated ERK1/2 phosphorylation seems to enhance MR nuclear shuttling and thereby transactivation activity (Grossmann et al 2005).…”
Section: Egfrmentioning
confidence: 99%